Professional Ethics and Their Role in Maintaining Accounting Integrity (gjstudies, 2017)
This research investigates the complex interplay between codified professional ethics andthe maintenance of accounting integrity, proposing a novel, multi-layered framework thatmoves beyond traditional compliance-based models. While existing literature often treatsethics as a static set of rules to prevent malfeasance, this study posits that integrity is adynamic, system-level property emerging from the interaction of individual moral reasoning, organizational culture, and institutional design. The paper introduces the concept of’Ethical Friction’—the productive tension between formal ethical codes and informal professional norms—as a critical mechanism for reinforcing integrity. Through a qualitative, crossdisciplinary methodology blending computational text analysis of disciplinary case archives(1995–2004) with insights from moral philosophy and institutional theory, we map the latentstructure of ethical reasoning in accounting practice. Our findings reveal that integrity breachesrarely stem from simple rule ignorance; instead, they correlate strongly with systemic failuresin what we term the ’Ethical Support Infrastructure’—the interconnected processes for deliberation, mentorship, and consequence navigation. The results demonstrate that the mostrobust integrity is found in environments where prescriptive codes are actively interpretedand contested, not merely followed. This challenges the prevailing audit-centric paradigm ofethics management and suggests a shift towards fostering deliberative communities of practice.The study’s primary contribution is a reframing of accounting ethics from a defensive, riskmitigation tool to a proactive, value-creating component of professional identity and organizational resilience, offering a new theoretical lens and practical diagnostic toolkit for assessingand strengthening the ethical foundations of financial reporting.